Isolation, characterization and quantitative proteomics analysis of chicken dendritic cells following infection with infectious bursal disease virus - Abd Rahaman, Nor Yasmin (2015)
Infectious bursal disease (IBD) is an extremely contagious and acute disease of young chicken cause by infectious bursal disease virus (IBDV). IBDV can infect B lymphocytes and macrophages. However, study on the involvement of chicken DCs during pathogen infection especially in IBDV infection has not been studied. Hypothesis of this study was chicken DCs are susceptible to IBDV infection and aimed to characterise the interaction between IBDV and chicken DCs as well as the proteomics profiles of chicken DCs during IBDV infections. DCs were isolated from bone marrow and spleen for in vitro and ex-vivo study, respectively. The isolated DCs were characterized based on morphology, viability and immunophenotyping while IBDV detection were performed based on immunofluorescence antibody test (IFAT), quantitative real-time polymerase chain reaction (qRT-PCR) and flow cytometry. qRT-PCR was also used to detect the expression of selected cytokines from IBDV-infected DCs. Quantitative proteomics using iTRAQ coupled with tandem LC-MS/MS approach and flow cytometry analysis were performed to quantify and validate differentially regulated proteins of BM-DCs. Morphologically, uninfected BM-DCs were rounded in shape whilst BM-DCs treated with LPS and vvIBDV showed stellate shapes. Both LPS-treated and vvIBDV-infected BM-DCs expressed high levels of CD86 and MHC class II antigens (>20 %) (p<0.05). In addition, vvIBDV-infected BM-DCs showed significantly higher numbers of apoptotic cells compared to LPS. Replication of vvIBDV was detected in the infected BM-DCs as evidenced by the increased in the expression of VP3 and VP4 antigens based on flow cytometry, qRT-PCR and IFAT. LPS was far more potent than vvIBDV in inducing the expression of IL-1β and IL-18, while the expressions of Th1-like cytokines, IFN- and IL-12α were significantly increased in vvIBDV treatment group. iTRAQ analysis coupled with LC-MS/MS analysis, detect the most abundant proteins (~40 %) with a known membranous localization. From the total of 283 proteins that were identified, 55, 47 and 32 proteins were differentially regulated at 3, 6 and 12 hpi, respectively, as a result of vvIBDV infection, with the fold difference ≥ 1.5 or ≤ 0.67 and ProtScore of more than 1.3 at 95 % confidence level. Most of the protein functions that were impaired at 3 hpi were related to signaling, stress response and immune response, for instance integrin α and β, heat shock proteins (HSPs) especially HSP90α and HSP60. Interestingly, no proteins related to signaling were activated at this time point. These findings give an indication that vvIBDV able to disrupt several important protein functions in order to infect BM-DCs at the early stage. Control and infected splenic DCs were distinct as infected DCs showed star like shape. In addition, infected splenic DCs in both vaccine strain and vvIBDV strain expressed higher CD86 and MHCII antigens of more than 30 % at day 5 pi. Meanwhile, VP3 and VP4 proteins of IBDV were readily detected in splenic DCs starting from day 3 pi in both vaccine and vvIBDV-infected groups via IFAT, flow cytometry and qRT-PCR, where the expression of these antigens were significantly higher in vvIBDV (p< 0.05). Splenic DCs infected with vaccine and vvIBDV strains also expressed elevated levels of pro-inflammatory cytokines and chemokines such as IL-1β and CXCLi2 as well as Th1-like cytokines such as IL-12α and IFNγ after day 3 onwards. In conclusion, chicken BM-DCs and splenic DCs are susceptible and permissive to IBDV infection. The virus infects DCs probably via common host proteins that are also found on other cells such as B cells and macrophages.